UPAYA MENINGKATKAN MOTORIK HALUS DENGAN AKTIVITAS BELAJAR MELALUI KEGIATAN MEWARNAI GAMBAR PADA ANAK USIA DINI DI KB. MENTARI BANGKIT KELURAHAN PARTEKER KECAMATAN PAMEKASAN KABUPATEN PAMEKASAN TAHUN PELAJARAN 2021/2022 - Erni Yuliastutik; M. Ridlwan; Ratno Abidin (PROCEEDING UMSURABAYA, 2022)
The purpose of this study was to determine the improvement of fine motor skills with learning activities through coloring pictures in early childhood at Kb. Mentari Rises, Parteker Village, Pamekasan District, Pamekasan Regency for the 2021/2022 Academic Year. Almost every child likes to draw and color, these activities are very beneficial for children because through this activity the children's fine motor skills are also trained and will be very useful when children start learning at school age. The research method used in this study uses qualitative methods. Research procedures in this study using observation guidelines are used to obtain data on improving the coloring of the image before the implementation of the action. The results of the research that have been carried out can be concluded that the percentage of fine motor skills in early childhood in family planning. Mentari Rises, Pamekasan District Parteker Sub-district The 2021/2022 academic year has increased. Keywords: early age; qualitative; observation; motor